The 6‐month effectiveness of Internet‐based guided self‐help for depression in adults with Type 1 and 2 diabetes mellitus. Issue 1 (4th August 2016) - Ebert, D. D.; Nobis, S.; Lehr, D.; Baumeister, H.; Riper, H.; Auerbach, R. P.; Snoek, F.; Cuijpers, P.; Berking, M.
Abstract: Aim: The aim of this research is to examine the 6‐month effects of an Internet‐based guided self‐help intervention for comorbid depressive symptoms in people with diabetes. Methods: Participants ( n = 260) with Type 1 or 2 diabetes and elevated depressive symptoms [Center for Epidemiological Studies Depression Scale (CES‐D) ≥ 23] were randomly assigned to a guided Internet‐based self‐help intervention or a control condition (treatment as usual + online psychoeducation about depression). The primary outcome was a change in depressive symptom severity (CES‐D) from baseline to 6‐month follow‐up. The secondary outcomes included numbers of people achieving treatment response (reliable change of depressive symptoms) and remission (CES‐D ≤ 16), as well as the effects on glycaemic control, diabetes‐related emotional distress and diabetes acceptance. Repeated measures analysis of variance examined between‐group differences using intent‐to‐treat principles. Results: Both conditions showed improvements in depression severity: intervention condition, d = 1.48 [95% confidence interval (95% CI): 1.21 to 1.76]; control condition d = 0.55 (95% CI: 0.30 to 0.80). Changes were significantly greater in the intervention condition with a large between‐group effect size ( d = 0.83, 95% CI: 0.57 to 1.08). Accordingly, effects on response [relative risk (RR) = 2.60 (95% CI: 2.01 to 3.36), P < 0.001] and remission [RR = 3.36 (95% CI: 2.98 to 5.44), P < 0.001] were in favour of the intervention group, as were differences in change in diabetes emotional distress ( d = 0.50, 95% CI: 0.04 to 0.54), and physical and mental functioning [Short Form Health Survey (SF‐12) Physical d = 0.27 (95% CI: 0.01 to 0.51) and SF‐12 Mental d = 0.68 (95% CI: 0.11 to 0.40)]. The intervention group was not superior with regard to glycaemic control, diabetes self‐management and diabetes acceptance. Conclusions: The trial indicates that Internet‐based guided self‐help treatments for depression in people with diabetes can have sustained effects on depressive symptoms, well‐being and emotional distress associated with diabetes. What's new?: Data on the long‐term effectiveness of treatments for comorbid depression and diabetes are scarce. Depressive symptoms in people with diabetes are undertreated. Results provide support for sustained benefits of Internet‐based guided self‐help for comorbid depressive symptoms and diabetes. Internet‐based guided self‐help could be one among other strategies to reduce the gap between the need for evidence‐based treatments and their availability for people with comorbid depression and diabetes.